Evaluating German business cycle forecasts under an asymmetric loss function - Jörg Döpke; Ulrich Fritsche; Boriss Siliverstovs (ETH Zurich, KOF Swiss Economic Institute, 2009)
Based on annual data for growth and inflation forecasts for Germany covering the time span from 1970 to 2007 and up to 17 different forecasts per year, we test for a possible asymmetry of the forecasters' loss function and estimate the degree of asymmetry for each forecasting institution using the approach of Elliot et al. (2005). Furthermore, we test for the rationality of the forecasts under the assumption of a possibly asymmetric loss function and for the features of an optimal forecast under the assumption of a generalized loss function. We find evidence for the existence of an asymmetric loss function of German forecasters only in case of pooled data and a quad-quad loss function. We cannot reject the hypothesis of rationality of the growth forecasts based on data for single institutions, but based on a pooled data set. The rationality of inflation forecasts frequently is rejected in case of single institutions and also for pooled data.
Keywords: C53; E42; 330; Business cycle forecast evaluation; asymmetric loss function; and rational expectations; Konjunkturprognose; Prognoseverfahren; Rationale Erwartung; Deutschland